Survei Minat dan Motivasi Mahasiswa Terhadap Ekstrakurikuler Futsal - Sulikan Sulikan (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2019)
Interest from someone is influenced by many factors, namely internally and externally. Motivation is one of the thing which is coming from inside. The goal of the research is to know how far the university students’ interest and motivation are in joining with extracurricular of futsal. The study was done through survey with two free variables, interest and motivation, while the instrument used to collect data were questionaires and documentation. Based on the analysis, it was found that the students’ responses ‘strongly agree’ in terms of their interest are 44.34%, ‘agree’ 35.97%, while the rest as their responses ‘disagree’ and ‘strongly disagree’ 16.74% and 2.94% respectively. Moreover, the students’ responses ‘strongly agree’ in terms of their motivation are 46.66%, ‘agree’ 35.53%, while the rest as their responses ‘disagree’ and ‘strongly disagree’ 14.79% and 3.01% respectively. Of the result, it can be concluded that the university students had high category of both interst and motivation. Therefore, it was suggested that they could defend their godd interest and motivation.